Wendell Berge papers - Berge, Wendell, 1903-1955.; Berge, George W., 1864-1925.
Correspondence, speeches, writings, articles, daily calendar, business diary, agenda, clippings, printed matter, photographs, and other papers relating primarily to Berge's official activities at the U.S. Dept. of Justice, culminating in his position as assistant attorney general in charge of the Antitrust Division under presidents Franklin D. Roosevelt and Harry S. Truman. Includes papers relating to Berge's school and college years and business records (1907) of his father, George W. Berge. Correspondents include Herbert Brownell, Oscar L. Chapman, Marquis W. Childs, Jonathan Daniels, Oscar R. Ewing, Felix Frankfurter, Robert Houghwout Jackson, and Earl Warren.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brownell, Herbert, -- 1904- -- Correspondence; Chapman, Oscar L. -- 1896-1978 -- Correspondence; Childs, Marquis W. -- 1903-1990 -- Correspondence; Daniels, Jonathan, -- 1902-1981 -- Correspondence; Ewing, Oscar R. -- 1899-1980 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Jackson, Robert Houghwout, -- 1892-1954 -- Correspondence; Warren, Earl, -- 1891-1974 -- Correspondence; United States. -- Department of Justice; United States. -- Department of Justice. -- Antitrust Division; Antitrust law; Lawyers; Public officials